Who Co-Moves The Islamic Stock Market of Indonesia -The US, The UK, or Japan? - M. Shabri Abd. Majid (Al-Iqtishad: Jurnal Ilmu Ekonomi Syariah, 2018)
This paper explores the dominance of world Islamic stock markets of Japan, the UK, and the US over the Islamic stock market of Indonesia. Daily Islamic stock indices of the UK, the US, Japan and Indonesia over the period 2000 to 2016 are utilized in the study. Both bivariate and multivariate Granger causalities based on Vector Error Correction Model (VECM) framework are adopted to empirically identify the co-movements among these Islamic stock markets. The study found that the Islamic stock markets of Indonesia, the UK, Japan, and the US are moving towards a greater level of integration. The Japanese Islamic stock market dominantly co-moved the Indonesian Islamic stocks, as compared to the UK and the US Islamic stock markets both in the bivariate and multivariate frameworks. This further implies that any developments in the Japanese financial market have to be given more consideration by the Indonesian authority in designing policy to stabilize and promote its Islamic stock market.DOI: 10.15408/aiq.v10i2.7288